PROBLEMATIKA PENGGUNAAN AKSARA ARAB - Zaki Ghufron (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
Arabic script is a system of written language used to symbolize the sounds of Arabic. It constitutes the category of written system of ortography and it is made based on the pronounciation of a sound independently or separated from the context of a word. As a result, there are latters arranged alphabetically, well-known as al-huruf al-hijaiyyah. All this time, Arabic script is acknowledged as a consistent language of the sound sign. It is understood considering that every Arabic letter has special character and it is completed by spelling rules. By such characters and spelling rules, every letter can write both its sound and its variances. It needs comprehensive understanding on the characters and the spelling rules of Arabic letters to write the sounds of Arabic scripts correctly. Without understanding it, the mistakes in writing a sound of Arabic scripts will appear. To avoid mistakes in writing the sounds of Arabic scripts, this article tries to explain the character of every Arabic letters as well as it spelling rules. This article also gives information about several Arabic letters that make difficulties for the users. Keywords: Arabic, Arabic script, al-huruf al-hijaiyyah